2005
DOI: 10.1128/aac.49.11.4561-4566.2005
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity of Human Neutrophil Defensin HNP-1 Analogs without Cysteines

Abstract: The antibacterial activity of human neutrophil defensin HNP-1 analogs without cysteines has been investigated. A peptide corresponding to the HNP-1 sequence without the six cysteines (HNP-1⌬C) exhibited antibacterial activity toward gram-negative and gram-positive bacteria. Truncated analogs wherein the nine N-terminal residues of HNP-1 and the remaining three cysteines were deleted (HNP-1⌬C18) or the G was replaced with A (HNP-1⌬C18A) also exhibited antibacterial activity. Substantial activity was observed fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
71
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(77 citation statements)
references
References 58 publications
(64 reference statements)
4
71
0
1
Order By: Relevance
“…The amino acid sequence of coprisin is very similar to that of the defensins, which are ϳ40-amino-acid peptides that have strong antibiotic activities against Gram-positive bacteria (24) that result from their ability to disrupt the membrane or suppress cell cycle signaling (48). Here, we showed that coprisin analogue treatment caused membrane damage to C. difficile but not to species of Bifidobacterium.…”
mentioning
confidence: 67%
“…The amino acid sequence of coprisin is very similar to that of the defensins, which are ϳ40-amino-acid peptides that have strong antibiotic activities against Gram-positive bacteria (24) that result from their ability to disrupt the membrane or suppress cell cycle signaling (48). Here, we showed that coprisin analogue treatment caused membrane damage to C. difficile but not to species of Bifidobacterium.…”
mentioning
confidence: 67%
“…The VR1 spectra demonstrated significantly more ␤-turns in 30 mM SDS micelles, with minima between 200 and 205 nm and maxima between 225 and 230 nm (11). In TFE, VR1 and VR2 exhibited a population having a ␤-hairpin conformation characterized by a negative ellipticity near 205 nm and a crossover at 200 nm (44). In sodium phosphate buffer, VR1, VR2, and VR3 showed a range of secondary structures, but the spectra suggested a population with ␤-sheet structure.…”
Section: Antimicrobial Activity the Mics Of Synthetic Peptides Againstmentioning
confidence: 99%
“…To further evaluate the antimicrobial potency of the peptides, the lethal concentration (LC) was also determined, as described previously (18). Briefly, the bacterial cells were washed three times with sterile phosphate-buffered saline ([PBS] 10 mM, pH 7.2) and resuspended in the same buffer.…”
Section: Methodsmentioning
confidence: 99%